2021
DOI: 10.1038/s41467-021-26512-4
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous dynamical disordering of borophenes in MgB2 and related metal borides

Abstract: Layered boron compounds have attracted significant interest in applications from energy storage to electronic materials to device applications, owing in part to a diversity of surface properties tied to specific arrangements of boron atoms. Here we report the energy landscape for surface atomic configurations of MgB2 by combining first-principles calculations, global optimization, material synthesis and characterization. We demonstrate that contrary to previous assumptions, multiple disordered reconstructions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…As a result, there is an enthalpic driving force toward clustering to passivate bonds. Analogously, another recent study showed that complex boron clustering is energetically favorable on the B-terminated (001) surface and kinetically accessible at room temperature due to the unpassivated nature of the boron surface bonds . However, it is worth noting that bonds are also undercoordinated at the Mg-rich edge, which is not prone to polyboron formation.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…As a result, there is an enthalpic driving force toward clustering to passivate bonds. Analogously, another recent study showed that complex boron clustering is energetically favorable on the B-terminated (001) surface and kinetically accessible at room temperature due to the unpassivated nature of the boron surface bonds . However, it is worth noting that bonds are also undercoordinated at the Mg-rich edge, which is not prone to polyboron formation.…”
Section: Resultsmentioning
confidence: 80%
“…Simultaneously, there are more B–B 4–7 arrangements, and these B atoms are more likely to be neutral as opposed to negatively charged. The change in charge reflects rearrangements of several B atoms to form clusters that have more elemental B character . Further signatures of polyboron clustering include the formation of units featuring B atoms multiply coordinated to other B atoms as well as H. These B atoms are also more generally neutral as opposed to the more common positive charge immediately following initialization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations